The sources of the monastic libraries funds in Lithuania on the end of XVIII - first half of XIX century - Pacevičius, Arvydas (Knygotyra, 1998)
The libraries of the Catholic cloisters was composed on the base of the Lithuanian nobility, magnates, hierarchy of Church, simple people gifts, which grew in the epoch of the Enlightenment. But the process of secularization in the society and annexation of the Grand Duchy of Lithuania by Russia in 1795 had to change situation. The article deals with sources of the funds of the cloisters libraries, which was influenced by the interior regulations of the monasteries, such as Regulas and Constitutions, foundations of libraries, financial sources, testimony of died Fraters, gifts of the monastic orders hierarchy and simple monks. The foundations of libraries as the depart institutions were in the medium of the Jesuits and Piarists, which revealed in the field of education. For example, David Pilchowski, S. J., in 1770 testified for the library of the „Collegium Nobilium” of the Jesuits in Vilnius his own book collection and 12 800 „auksinas” (in Polish „zloty”); it was action of foundation. But the other monastic Orders (Bernardines, Dominicans, Franciscans, Carmelites) had libraries only like „one part of foundation capital – stock of all cloister”. More precise financing of the libraries was not defined in the Regulas of the monastic Orders, and the problem of financing was solved in the frame of the Lithuanian monastic provinces and in the cloisters themselves. The cloister of Piarists in Vilnius in 1777–1780 for this aim intended from 24 to 62 „auksinas”, and in 1828–50 roubles each year. Missionaries, but till 1789, each year the percents of the capitals kept in the Bank of Paris intended for purchase of new books. But the most important source of the funds were the book collections of the monks, which even without testimony were included into the libraries of the cloisters. The memorial and dedicating inscriptions and also the titles of the personal books of the monks, included into the catalogues of the libraries testifies the spread of the bibliophilia not only among the Dominicans, such as Dominicus Siwicki, Zygmunt Piskowski. Book collecting took place in the medium of the Bernardines (Juventalis Chrkiewicz, Fabijonas Barkauskis, Kiprijonas Lukauskas) and also among Franciscans (Felix Towianski, Antoni Paszkiewicz, Hugo Rodziewicz, Antoni Kocieł, Jozef Rypinski). They brought the books from the trips to Jerusalem and to the General Capitulas, which took places in the West Europe. At the beginning of the 19th century, when the modern forms of the book trade and also the functionation of books in society spread all over Europe, in the monasteries creatively coexisted the tradition with the experience of the new epoch. The level of this coexisting is the object of the future researches.